ERKs and JNKs mediate hydrogen peroxide-induced Egr-1 expression and nuclear accumulation in H9c2 cells - Aggeli, I K S; Beis, I; Gaitanaki, C (Physiological research, 2010)
One of the most significant insults that jeopardize cardiomyocyte homeostasis is a surge of reactive oxygen species (ROS) in the failing myocardium. Early growth response factor-1 (Egr-1) has been found to act as a transcriptional regulator in multiple biological processes known to exert deleterious effects on cardiomyocytes. We thus investigated the signaling pathways involved in its regulation by H2O2. Egr-1 mRNA levels were found to be maximally induced after 2 h in H2O2-treated H9c2 cells. Egr-1 respective response at the protein level, was found to be maximally induced after 2 h of treatment with 200 microM H2O2, remaining elevated for 6 h, and declining thereafter. H2O2-induced upregulation of Egr-1 mRNA and protein levels was ablated in the presence of agents inhibiting ERKs pathway (PD98059) and JNKs (SP600125, AS601245). Immunofluorescent experiments revealed H2O2-induced Egr-1 nuclear sequestration to be also ERK- and JNK-dependent. Overall, our results show for the first time the fundamental role of ERKs and JNKs in regulating Egr-1 response to H2O2 treatment in cardiac cells at multiple levels: mRNA, protein and subcellular distribution. Nevertheless, further studies are required to elucidate the specific physiological role of Egr-1 regarding the modulation of gene expression and determination of cell fate.
Keywords: Animals; Hydrogen Peroxide; JNK Mitogen-Activated Protein Kinases; buněčné linie; Active Transport, Cell Nucleus; inhibitory proteinkinas; Myocytes, Cardiac; Up-Regulation; Time Factors; časové faktory; peroxid vodíku; Cell Nucleus; fluorescenční protilátková technika; Fluorescent Antibody Technique; upregulace; messenger RNA; aktivní transport - buněčné jádro; Cell Line; RNA, Messenger; JNK mitogenem aktivované proteinkinasy; buněčné jádro; Protein Kinase Inhibitors; protein 1 časné růstové odpovědi; Early Growth Response Protein 1; krysa rodu Rattus; zvířata; extracelulárním signálem regulované MAP kinasy; Rats; kardiomyocyty; Extracellular Signal-Regulated MAP Kinases